KENDALI TORKA PREDIKTIF DENGAN PREDIKSI DUA LANGKAH MOTOR INDUKSI YANG DICATU OLEH SEBUAH INVERTER TIGA FASE - Adam, Ahmad Antares; Arifin, Yusnaini; Mukhlis, Baso; Kali, Agustinus; Mar'atussolihah, Ratih (Foristek, 2023)
The predictive torque control (PTC) technique of electric motor drive is based on the principle that the determined optimum voltage vector will be applied to the motor in the next cycle. If a three-phase inverter is used, this inverter can only realize eight different switching states. One of the eight switching states is used as the optimum inverter switching state for the next cycle. PTC with one-step prediction cannot obtain an experimental motor speed control, because in the real-time implementation, there is a single sampling delay between input and optimal actuation due to a large number of real time calculations. The delay time problem could be solved by modifying the optimization steps by using the two-step prediction of PTC model. The experimental results show that the motor can follow the reference speed and command torque in the step response and variable speed experiments. In variable speed experiment, good speed and torque dynamics can be achieved by selecting the proportional gain value that corresponds to the motor speed